The financing of local government in the people's republic of China: Stimulus loan wanes and shadow banking waxes - Zhuo Chen; Zhiguo He; Chun Liu (Asian Development Bank Institute (ADBI), 2018)
China's four-trillion-yuan stimulus package fueled by bank loans in 2009 has led to the rapid growth of shadow banking activities in China after 2012. The local governments in China financed the stimulus plan mainly through bank loans in 2009, and resorted to non-bank debt financing after 2012 given the mounting rollover pressure from bank debt coming due, a manifestation of the stimulusloan- hangover effect. Cross-sectionally, provinces with abnormally greater bank loan growth in 2009 experienced more Municipal Corporate Bonds issuance during 2012-2015, as well as more shadow banking activities including Entrusted loans and Wealth Management Products. We highlight the market forces behind the regulation changes on local government debt post 2012, together with the expedited reform on interest rate liberalization during that period.
Keywords: E61; G21; H72; O17; 330; local government financing vehicles; municipal corporate bonds; shadow banking in China